Application of the Traffic Separation Scheme (TSS) in the Sunda Strait: A Literature Review - Nursyamsu Nursyamsu; Vidiana Anggeranika; Syairi Anwar; Rudi Harun Irwansyah (Al-Makki Publisher, 2025)
The Sunda Strait is one of Indonesia’s strategic maritime choke points, connecting the Indian Ocean with the Java Sea. The high volume of vessel traffic, complex geographical conditions, and limited navigation facilities pose significant risks of maritime accidents. The International Maritime Organization (IMO) approved the implementation of a Traffic Separation Scheme (TSS) in the Sunda Strait on July 1, 2020, aimed at enhancing navigational safety and preventing marine pollution. This study employs a literature review method by analyzing international regulations, national laws, technical reports, and previous research. The review focuses on four aspects: navigational safety, traffic efficiency, environmental protection, and implementation challenges. Findings indicate that the TSS significantly contributes to reducing collision risks and improving maritime traffic order. However, challenges remain, including limited Vessel Traffic Service (VTS) facilities, compliance by foreign vessels, and inter-agency coordination. This study emphasizes the need for improved navigation infrastructure, AIS-based monitoring, and continuous awareness programs to optimize TSS implementation in the Sunda Strait.